Horizons : an exhibition report presented in alignment of the requirements for the Master of Maori Visual Arts, Massey University, Palmerston North, 'Aotearoa' New Zealand - Puente, Tyler (Massey University, 2020)
When I first committed to the medium printmaking, I thought I was crazy do so because I instantly realized this medium is still fresh for Indigenous printmakers to attempt. Not many Diné practice printmaking today, unlike non-Indigenous printmakers who have their histories to them to support what they print for viewers to read. Where I remember first learning about the history of printmaking, it seems that the medium is generally taught to all through a westernized context that avoids informing printmaking majors about the indigenous people’s contributions to the medium. Printing resources are not well documented for Diné printmakers to reference back to support images once they’re processed through the printing press. I had to determine which art source could be supportive to ground my art research project. I concluded petroglyphs near home might guide me throughout this entire process.--Pages 9-10
Copyright holders of copyrighted material may request its removal via the Take Down Request link below.
Keywords: 360699 Visual arts not elsewhere classified